InGaN red light LED device based on variable Al component electron barrier layer to enhance polarization effect and preparation method thereof

By controlling the Al component content and thickness of the p-type AlGaN electron barrier layer, the polarization effect is enhanced, and the problems of low luminescence efficiency and difficulty in achieving long-wavelength emission in the InGaN red LED are solved, and the long-wavelength emission and high luminescence intensity of the low In component active region are achieved.

CN119730492AActive Publication Date: 2025-03-28TSINGHUA UNIVERSITY +1

Patent Information

Application Number
CN202411800089.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing InGaN red LEDs have low luminous efficiency and are difficult to achieve long-wavelength emission, mainly due to poor quality of the active region of high In components and the decomposition of InN at high temperatures.

Method used

By controlling the Al component content and thickness in the p-type AlGaN electron barrier layer, the polarization effect is enhanced, and the long wavelength emission of the active region of the low In component is achieved.

Benefits of technology

The luminescence wavelength and luminescence intensity of InGaN red LED are improved, and the problem of poor crystal quality in the active region of high In component is avoided, and a high luminescence efficiency is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730492A_ABST
    Figure CN119730492A_ABST
Patent Text Reader

Abstract

The invention discloses an InGaN red light LED device based on a variable Al component electron barrier layer to enhance a polarization effect and a preparation method thereof. The InGaN red light LED device sequentially comprises a substrate, a low-temperature buffer layer, a high-temperature buffer layer, a non-doped GaN layer, an n-type doped GaN layer, a superlattice layer and / or a low-temperature GaN layer, a quantum well active region, a p-type AlGaN electron barrier layer and a p-type region from bottom to top, wherein the atomic percentage content of Al in the p-type AlGaN electron barrier layer is 22%-30%, and the thickness of the p-type AlGaN electron barrier layer is 5 nm to 15 nm. By controlling the p-type AlGaN electron barrier layer, long-wavelength emission of the low-In-component active region can be achieved, and the problems that a high-In-component active region of an existing long-wavelength InGaN red light LED is poor in crystal quality and difficult to obtain and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an InGaN red light LED device based on an electron blocking layer with a variable Al composition to enhance polarization effect and a preparation method thereof, belonging to the technical field of light emitting diodes. Background Art

[0002] In the field of light-emitting diodes (LEDs), the development of new display technologies, represented by AR / VR, has placed new demands on display devices, one of the most notable characteristics of which is a significant increase in resolution. Currently, the blue, green InGaN, and red AlGaInP technologies used in Micro-LEDs are relatively mature. However, the high carrier mobility of AlGaInP materials leads to more carriers participating in non-radiative recombination on the sidewalls as chip size decreases, rapidly decreasing luminous efficiency. Furthermore, monolithic integration of AlGaInP and InGaN materials presents difficulties, so the red Micro-LEDs required for full-color Micro-LED die integration still need improvement.

[0003] Therefore, InGaN-based red LEDs have become a hot topic of concern in industry and academia. Due to the low carrier mobility in GaN materials, their size effect is relatively insignificant, and their performance is relatively better at high temperatures. In addition, the use of InGaN materials for all colors perfectly solves the difficulties of monolithic integration of RGB three-color LEDs. Zhuang et al. reported that by introducing AlN / AlGaN barriers to compensate for strain and hybrid QW, they achieved the growth of high-In content InGaN, with an LED peak wavelength of 633nm and an external quantum efficiency of 1.6% (Z. Zhuang, D. Iida, and K. Ohkawa, "InGaN-based red light-emitting diodes: from traditional to micro-LEDs," Jpn. J. Appl. Phys. 61 (SA) (2022).). Sang et al. reported an orange-red Micro-LED with a chip size of 40 μm, an emission wavelength of 603 nm, and a peak electro-optical conversion efficiency of 4.3% achieved through a tunnel junction (YM Sang, Z. Zhuang, K. Xing, DQ Zhang, JJ Yan, ZY Jiang, CX Li, K. Chen, Y. Ding, T. Tao, D. Iida, K. Wang, C. Li, K. Huang, K. Ohkawa, R. Zhang, and B. Liu, “High-temperature performance of InGaN-based amber micro-light-emitting diodes using anepitaxial tunnel junction contact,” Appl. Phys. Lett. 124(14)(2024).).Chen et al. reported a composite buffer layer to increase the surface lattice constant of GaN, successfully improving the incorporation efficiency of In in the active region and achieving an InGaN red mini-LED chip with a peak wavelength of 629 nm and an external quantum efficiency of 7.4% (ZYChen, BW Sheng, F. Liu, SF Liu, D. Li, ZX Yuan, T. Wang, X. Rong, JS Huang, JY Qiu, WJ Liang, CL Zhao, L. Yan, JS Hu, SP Guo, WK Ge, B. Shen, and XQ Wang, “High-Efficiency InGaN Red Mini-LEDs on Sapphire Toward Full-Color Nitride Displays: Effect of Strain Modulation,” Adv. Funct. Mater. 33(26)(2023).).

[0004] In existing technologies, the long-wavelength InGaN red light active region usually requires an In component of 35% or even 40%, which is a huge challenge for epitaxy. The lattice mismatch between GaN and InN reaches 11%, and such a high In component is bound to cause a decline in the quality of the active region and produce a large number of defects and non-radiative recombination centers, affecting the luminous efficiency. In terms of growth temperature, the bond energy of the In-N chemical bond is smaller than that of Ga-N. InN is more susceptible to decomposition and desorption at high temperatures, so a lower growth temperature is required, but low-temperature epitaxy usually leads to insufficient atomic migration and further deterioration of crystal quality. In summary, long-wavelength InGaN red light LEDs are very difficult to achieve, and their efficiency in existing reports does not exceed 10%, which is unable to meet current needs. Summary of the Invention

[0005] To address at least one of the aforementioned technical issues, the present invention provides an InGaN red LED device and its fabrication method, utilizing a variable Al-composition electron-blocking layer to enhance polarization effects. By controlling the p-type AlGaN electron-blocking layer, the present invention enables long-wavelength emission from a low-In-composition active region.

[0006] To achieve the above objectives, the first aspect of the present invention provides an InGaN red light LED device based on a variable Al composition electron blocking layer to enhance the polarization effect. The device comprises, from bottom to top, a substrate, a low-temperature buffer layer grown on the substrate, a high-temperature buffer layer grown on the low-temperature buffer layer, an undoped GaN layer grown on the high-temperature buffer layer, an n-type doped GaN layer grown on the undoped GaN layer, a superlattice layer and / or a low-temperature GaN layer grown on the n-type doped GaN layer, a quantum well active region grown on the superlattice layer or the low-temperature GaN layer, a p-type AlGaN electron blocking layer grown on the quantum well active region, and a p-type region grown on the p-type AlGaN electron blocking layer; wherein the quantum well active region comprises a composite layer of a red light quantum well layer and a red light barrier layer; based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer is 22-30%; and the thickness of the p-type AlGaN electron blocking layer is 5-15 nm.

[0007] The function of the electron blocking layer in the prior art is mainly to prevent electrons from overflowing, thereby improving the luminous efficiency. However, the inventors have discovered that by controlling the Al component content and the thickness of the p-type AlGaN electron blocking layer in the range of the present invention, the polarization effect can be enhanced, thereby increasing the luminous wavelength while taking into account a higher luminous intensity. If the Al component content in the p-type AlGaN electron blocking layer is higher than the range of the present invention, the luminous intensity of the InGaN red light LED will be reduced; if the Al component content in the p-type AlGaN electron blocking layer is lower than the range of the present invention, it will be difficult to achieve the effect of increasing the luminous wavelength. If the thickness of the p-type AlGaN electron blocking layer is higher than the range of the present invention, it will make it difficult for holes to be injected into the red light well, resulting in a decrease in luminous intensity; if the thickness of the p-type AlGaN electron blocking layer is lower than the range of the present invention, the electron blocking ability is poor and the polarization effect is weakened, thereby reducing the luminous intensity and the luminous wavelength.

[0008] It should be noted that, in the present invention, InGaN refers to indium gallium nitride, and does not specifically refer to the ratio of In, Ga, and N elements therein.

[0009] According to a specific embodiment of the present invention, preferably, the substrate includes a c-plane sapphire substrate or a c-plane GaN substrate to ensure that the GaN material and the InGaN material on the substrate are also polar plane materials.

[0010] According to a specific embodiment of the present invention, preferably, the size of the substrate is 2-8 inches, for example, 2 inches, 4 inches, 6 inches or 8 inches.

[0011] According to a specific embodiment of the present invention, preferably, the material of the low-temperature buffer layer includes GaN material, and the growth temperature is 550-600°C; the material of the high-temperature buffer layer includes GaN material, and the growth temperature is 1000-1050°C.

[0012] According to a specific embodiment of the present invention, preferably, the thickness of the low-temperature buffer layer is 0.2-0.5 μm; the thickness of the high-temperature buffer layer is 0.1-0.5 μm.

[0013] According to a specific embodiment of the present invention, preferably, the thickness of the undoped GaN layer is 2-4 μm.

[0014] According to a specific embodiment of the present invention, preferably, the thickness of the n-type doped GaN layer is 1-3 μm.

[0015] According to a specific embodiment of the present invention, preferably, the doping element in the n-type doped GaN layer is silicon, and the doping concentration is 1E18-5E18 cm -3 .

[0016] According to a specific embodiment of the present invention, preferably, the InGaN red light LED device includes a superlattice layer and a low-temperature GaN layer grown on the n-type doped GaN layer, and the low-temperature GaN layer is grown on the superlattice layer, and the quantum well active region is grown on the low-temperature GaN layer.

[0017] According to a specific embodiment of the present invention, preferably, the superlattice layer includes an InGaN / GaN superlattice with a period number of 2-30 periods.

[0018] According to a specific embodiment of the present invention, preferably, the InGaN / GaN superlattice includes an InGaN layer with a thickness of 1-3 nm and a GaN layer with a thickness of 2-15 nm.

[0019] According to a specific embodiment of the present invention, preferably, based on the total number of In and Ga atoms in the InGaN layer in the InGaN / GaN superlattice being 100%, the content of In in the InGaN layer is 3-8%.

[0020] According to a specific embodiment of the present invention, preferably, the superlattice layer is a silicon-doped superlattice layer or an undoped superlattice layer. More preferably, the superlattice layer is a silicon-doped superlattice layer with a doping concentration of 1E18-5E18cm -3 .

[0021] According to a specific embodiment of the present invention, preferably, the material of the low-temperature GaN layer includes undoped GaN material, and the growth temperature is 700-850°C, more preferably 820-840°C.

[0022] According to a specific embodiment of the present invention, preferably, the thickness of the low-temperature GaN layer is 5-100 nm.

[0023] According to a specific embodiment of the present invention, preferably, the quantum well active region includes a composite layer of a red light quantum well layer and a red light barrier layer with a period number of 1-5 periods.

[0024] According to a specific embodiment of the present invention, preferably, the material of the red light quantum well layer includes an undoped InGaN material, wherein the atomic percentage of In is 25-35%, based on the total atomic number of In and Ga in the undoped InGaN material being 100%. The red light quantum well layer is the main light-emitting structure under electrical injection.

[0025] According to a specific embodiment of the present invention, preferably, the thickness of the red light quantum well layer is 2-4 nm.

[0026] According to a specific embodiment of the present invention, preferably, the material of the red light barrier layer includes undoped GaN material or undoped InGaN material, and the atomic percentage of In in the red light barrier layer is 0-10%, based on the total number of atoms of In (if contained) and Ga in the undoped GaN material or the undoped InGaN material being 100%.

[0027] According to a specific embodiment of the present invention, preferably, the thickness of the red light barrier layer is 3-20 nm.

[0028] According to a specific embodiment of the present invention, preferably, the quantum well active region further includes a composite layer of a blue light quantum well layer-blue light barrier layer with a period number of 1-5 periods, and the composite layer of the red light quantum well layer-red light barrier layer is grown on the composite layer of the blue light quantum well layer-blue light barrier layer.

[0029] According to a specific embodiment of the present invention, preferably, the material of the blue light quantum well layer includes undoped InGaN material, and the atomic percentage of In is 3-10%, based on the total atomic number of In and Ga in the undoped InGaN material being 100%.

[0030] According to a specific embodiment of the present invention, preferably, the thickness of the blue light quantum well layer is 2-4 nm.

[0031] According to a specific embodiment of the present invention, preferably, the material of the blue light barrier layer includes undoped GaN material or undoped InGaN material, and the atomic percentage of In in the blue light barrier layer is 0-5%, based on the total number of atoms of In (if contained) and Ga in the undoped GaN material or the undoped InGaN material being 100%.

[0032] According to a specific embodiment of the present invention, preferably, the thickness of the blue light barrier layer is 3-20 nm.

[0033] According to a specific embodiment of the present invention, preferably, based on the total number of Al and Ga atoms in AlGaN as 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer is 25-29%, more preferably 26-28%, and further preferably 27%; the thickness of the p-type AlGaN electron blocking layer is 8-12 nm, more preferably 9.5-10.5 nm, and further preferably 10 nm.

[0034] According to a specific embodiment of the present invention, preferably, the p-type AlGaN electron blocking layer is doped with Mg element, and the doping concentration of Mg is 1E18-2E20 cm -3 .

[0035] According to a specific embodiment of the present invention, preferably, the material of the p-type region includes GaN material and is doped with Mg element, and the doping concentration of Mg is 1E18-2E20 cm -3 .

[0036] According to a specific embodiment of the present invention, preferably, the thickness of the p-type region is 100-300 nm.

[0037] A second aspect of the present invention provides a method for preparing the above-mentioned InGaN red light emitting diode device based on a variable Al composition electron blocking layer to enhance the polarization effect, comprising the following steps:

[0038] (1) epitaxially growing a low-temperature buffer layer, a high-temperature buffer layer, an undoped GaN layer, an n-type doped GaN layer, and a superlattice layer and / or a low-temperature GaN layer on a substrate in sequence;

[0039] (2) epitaxially growing a quantum well active region on the superlattice layer or the low-temperature GaN layer;

[0040] (3) Epitaxially growing a p-type AlGaN electron blocking layer and a p-type region on the quantum well active region in sequence, thereby obtaining the InGaN red light LED device based on the electron blocking layer with variable Al composition to enhance the polarization effect.

[0041] According to a specific embodiment of the present invention, preferably, step (1) includes: using an MOCVD (metal organic chemical vapor deposition) epitaxial growth method to sequentially epitaxially grow a low-temperature buffer layer, a high-temperature buffer layer, an undoped GaN layer, an n-type doped GaN layer, a superlattice layer and / or a low-temperature GaN layer on a substrate, and the growth conditions include: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an In source flow rate of 20-300 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the low-temperature buffer layer of 550-600°C; a growth temperature of the high-temperature buffer layer of 1000-1050°C; a growth temperature of the undoped GaN layer of 1000-1050°C; a growth temperature of the n-type doped GaN layer of 1000-1050°C; a growth temperature of the superlattice layer of 700-850°C; and a growth temperature of the low-temperature GaN layer of 700-850°C. More preferably, the doping element in the n-type doped GaN layer is silicon, the doping source includes silane, and the doping concentration is 1E18-5E18 cm -3 More preferably, the superlattice layer is a silicon-doped superlattice layer, the doping source includes silane, and the doping concentration is 1E18-5E18 cm -3 More preferably, the growth temperature of the low-temperature GaN layer is 820-840°C.

[0042] According to a specific embodiment of the present invention, preferably, step (2) includes: epitaxially growing a quantum well active region on the superlattice layer or the low-temperature GaN layer by an MOCVD epitaxial growth method, which includes a composite layer of a red light quantum well layer-a red light barrier layer, and the growth conditions include: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an In source flow rate of 20-500 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the red light quantum well layer of 650-730°C; and a growth temperature of the red light barrier layer of 750-900°C. More preferably, the quantum well active region further includes a composite layer of a blue light quantum well layer-blue light barrier layer with a period number of 1-5 periods, and the composite layer of the red light quantum well layer-red light barrier layer is grown on the composite layer of the blue light quantum well layer-blue light barrier layer; the growth conditions of the composite layer of the blue light quantum well layer-blue light barrier layer include: growth pressure of 50-1000 mbar, Ga source flow rate of 10-200 sccm; In source flow rate of 20-500 sccm; N source flow rate of 2-10 slm; carrier gas of nitrogen or hydrogen; growth temperature of the blue light quantum well layer of 720-750°C; growth temperature of the blue light barrier layer of 750-900°C.

[0043] According to a specific embodiment of the present invention, preferably, step (3) includes: epitaxially growing a p-type AlGaN electron blocking layer and a p-type region on the quantum well active region using an MOCVD epitaxial growth method, wherein the growth conditions include: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an Al source flow rate of 10-400 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the p-type AlGaN electron blocking layer of 900-1000°C; and a growth temperature of the p-type region of 900-1000°C. More preferably, the p-type AlGaN electron blocking layer is doped with Mg, the doping source includes Cp2Mg (bis(cyclopentadienyl)magnesium), and the Mg doping concentration is 1E18-2E20 cm -3 More preferably, the p-type region is doped with Mg element, the doping source includes Cp2Mg (bis(cyclopentadienyl)magnesium), and the Mg doping concentration is 1E18-2E20 cm -3 .

[0044] According to a specific embodiment of the present invention, preferably, the Ga source in steps (1) to (3) may include TMGa (trimethyl gallium) or the like, the N source may include ammonia or the like, the In source may include TMIn (trimethyl indium) or the like, and the Al source may include TMAl (trimethyl aluminum) or the like.

[0045] The present invention has at least the following beneficial effects:

[0046] The present invention provides an InGaN red light LED device based on a variable Al composition electron blocking layer to enhance the polarization effect and a preparation method thereof. Due to the energy level structure and carrier blocking effect of the p-type AlGaN electron blocking layer (EBL) of the present invention, in addition to improving the wave function overlap of electron-hole pairs in the active region and increasing the luminous intensity of the LED, it also intensifies the polarization electric field in the active region, thereby increasing the degree of energy band tilt in the active region, reducing the equivalent band gap width of the InGaN material, and thus increasing the emission wavelength of the InGaN red light LED, thereby obtaining a long-wavelength InGaN red light LED with a low In composition active region. By controlling the Al composition content and thickness of the p-type AlGaN electron blocking layer within the range of the present invention, the emission wavelength of the LED is red-shifted, and long-wavelength emission from the low In composition active region can be achieved, avoiding the problems of existing long-wavelength InGaN red light LEDs with high In composition active regions, such as poor crystal quality, which affects luminous efficiency, and difficulty in obtaining. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Schematic diagram of the structure of an InGaN red light LED device based on an electron blocking layer with a variable Al composition to enhance the polarization effect according to an embodiment of the present invention.

[0048] Figure 2 Flow chart of the preparation process of the Micro-LED chip according to an embodiment of the present invention.

[0049] Figure 3 These are the luminescence photos of the point indium sphere test of Example 1 and the integrating sphere light collection spectra of Example 1 and Comparative Examples 1-3.

[0050] Figure 4 These are the performance test results of the Mciro-LED chip made from the InGaN red LED device of Example 1 under different electrical injection conditions.

[0051] Figure 5 Peak wavelength curves of the Micro-LED chips made from the InGaN red LED devices of Example 1 and Comparative Example 1 under different electrical injections.

[0052] Figure 6 This is the peak wavelength curve of LEDs with different Al component contents in Test Example 3.

[0053] Description of Figure Numbers:

[0054] 1-substrate; 2-low-temperature buffer layer; 3-high-temperature buffer layer; 4-undoped GaN layer; 5-n-type doped GaN layer; 6-superlattice layer; 7-low-temperature GaN layer; 8-quantum well active region; 9-p-type AlGaN electron blocking layer; 10-p-type region;

[0055] 801 - a composite layer of a blue light quantum well layer and a blue light barrier layer; 802 - a composite layer of a red light quantum well layer and a red light barrier layer. DETAILED DESCRIPTION

[0056] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.

[0057] Example 1

[0058] This embodiment provides an InGaN red light LED device based on a variable Al composition electron blocking layer to enhance the polarization effect, such as Figure 1 As shown, it includes, from bottom to top: a substrate 1, a low-temperature buffer layer 2 grown on the substrate 1, a high-temperature buffer layer 3 grown on the low-temperature buffer layer 2, an undoped GaN layer 4 grown on the high-temperature buffer layer 3, an n-type doped GaN layer 5 grown on the undoped GaN layer 4, a superlattice layer 6 grown on the n-type doped GaN layer 5, a low-temperature GaN layer 7 grown on the superlattice layer 6, a quantum well active region 8 grown on the low-temperature GaN layer 7, a p-type AlGaN electron blocking layer 9 grown on the quantum well active region 8, and a p-type region 10 grown on the p-type AlGaN electron blocking layer 9.

[0059] In this embodiment, the substrate 1 is a c-plane sapphire substrate with a size of 4 inches. The material of the low-temperature buffer layer 2 includes GaN material, and the growth temperature is 575°C. The thickness of the low-temperature buffer layer 2 is 0.4 μm. The material of the high-temperature buffer layer 3 includes GaN material, and the growth temperature is 1020°C. The thickness of the high-temperature buffer layer 3 is 0.2 μm. The thickness of the undoped GaN layer 4 is 3 μm. The thickness of the n-type doped GaN layer 5 is 2 μm. The doping element in the n-type doped GaN layer 5 is silicon, and the doping concentration is 1E18 cm -3 .

[0060] The superlattice layer 6 includes an InGaN / GaN superlattice with a period number of 24. The InGaN / GaN superlattice includes an InGaN layer with a thickness of 1.3 nm and a GaN layer with a thickness of 2.5 nm. The material of the InGaN layer includes InGaN. 0.05 Ga 0.95 N (i.e., the total number of In and Ga atoms in the InGaN layer of the InGaN / GaN superlattice is 100%, and the In content in the InGaN layer is 5%). The superlattice layer 6 is a silicon-doped superlattice layer 6 with a doping concentration of 1E18 cm -3 .

[0061] The material of the low-temperature GaN layer 7 includes non-doped GaN material, and the growth temperature is 830° C. The thickness of the low-temperature GaN layer 7 is 7 nm.

[0062] The quantum well active region 8 includes a composite layer 801 of a blue light quantum well layer-blue light barrier layer with a period number of 2 periods, and a composite layer 802 of a red light quantum well layer-red light barrier layer with a period number of 1 period grown on the composite layer 801 of the blue light quantum well layer-blue light barrier layer.

[0063] The materials of the blue light quantum well layer include non-doped In 0.05 Ga 0.95 N (that is, based on the total number of In and Ga atoms in the non-doped InGaN material being 100%, the atomic percentage of In is 5%). The thickness of the blue light quantum well layer is 3 nm.

[0064] The blue light barrier layer is made of non-doped GaN material and has a thickness of 12 nm.

[0065] The material of the red light quantum well layer includes non-doped In 0.30 Ga 0.70 N (ie, the atomic percentage of In is 30%, based on the total atomic number of In and Ga in the non-doped InGaN material being 100%). The thickness of the red light quantum well layer is 3 nm.

[0066] The material of the red light barrier layer includes non-doped GaN material and has a thickness of 3 nm.

[0067] Taking the total number of Al and Ga atoms in AlGaN as 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer 9 is 27%, that is, the material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.27 Ga 0.73 N. The thickness of the p-type AlGaN electron blocking layer is 10 nm. The p-type AlGaN electron blocking layer 9 is doped with Mg element, and the Mg doping concentration is 1E20 cm -3 .

[0068] The material of the p-type region 10 includes GaN material and is doped with Mg element, and the doping concentration of Mg is 1E20 cm -3 The thickness of the p-type region 10 is 160 nm.

[0069] This embodiment also provides a method for preparing the above-mentioned InGaN red light emitting diode device based on a variable Al composition electron blocking layer to enhance the polarization effect, which comprises the following steps:

[0070] (1) A low-temperature buffer layer 2, a high-temperature buffer layer 3, an undoped GaN layer 4, an n-type doped GaN layer 5, a superlattice layer 6, and a low-temperature GaN layer 7 are epitaxially grown on a substrate 1 in sequence using an MOCVD epitaxial growth method. The growth conditions include: a growth pressure of 200 mbar, a Ga source flow rate of 67 sccm, an In source flow rate of 60 sccm, and an N source flow rate of 5 slm; hydrogen as the carrier gas; a growth temperature of 575°C for the low-temperature buffer layer 2; a growth temperature of 1020°C for the high-temperature buffer layer 3; a growth temperature of 1040°C for the undoped GaN layer 4; and a growth temperature of 1040°C for the n-type doped GaN layer 5. The doping element in the n-type doped GaN layer 5 is silicon, the doping source is silane, and the doping concentration is 1E18 cm -3 The growth temperature of the superlattice layer 6 is 830°C. The superlattice layer 6 is a silicon-doped superlattice layer 6. The doping source is silane, and the doping concentration is 1E18 cm -3 The growth temperature of the low-temperature GaN layer 7 is 830°C.

[0071] (2) The MOCVD epitaxial growth method is adopted to epitaxially grow the quantum well active region 8 on the low-temperature GaN layer 7. The growth conditions of the composite layer 801 of the blue quantum well layer-blue barrier layer include: growth pressure of 200 mbar, Ga source flow rate of 67 sccm; In source flow rate of 60 sccm; N source flow rate of 5 slm; carrier gas of nitrogen; growth temperature of the blue quantum well layer of 730°C; growth temperature of the blue barrier layer of 850°C; growth conditions of the composite layer 802 of the red quantum well layer-red barrier layer include: growth pressure of 200 mbar, Ga source flow rate of 25 sccm; In source flow rate of 340 sccm; N source flow rate of 5 slm; carrier gas of nitrogen; growth temperature of the red quantum well layer of 690°C; growth temperature of the red barrier layer of 870°C;

[0072] (3) Using MOCVD epitaxial growth, a p-type AlGaN electron blocking layer 9 and a p-type region 10 are sequentially epitaxially grown on the quantum well active region 8. The growth conditions include: a growth pressure of 200 mbar, a Ga source flow rate of 67 sccm, an Al source flow rate of 50 sccm, and a N source flow rate of 5 slm; a carrier gas of hydrogen; a growth temperature of 945°C for the p-type AlGaN electron blocking layer 9, and Mg is doped in the p-type AlGaN electron blocking layer 9. The doping source is Cp2Mg, and the Mg doping concentration is 1E20 cm -3 The growth temperature of the p-type region 10 is 945°C. The p-type region 10 is doped with Mg. The doping source is Cp2Mg. The Mg doping concentration is 1E20 cm -3 , obtaining the InGaN red light LED device based on the electron blocking layer with variable Al composition to enhance the polarization effect;

[0073] Wherein, the Ga source in steps (1) to (3) is TMGa, the N source is ammonia, the In source is TMIn, and the Al source is TMAl.

[0074] The InGaN red LED device prepared by the above method is an epitaxial wafer, and conventional methods in the art are used, such as Figure 2 As shown, the prepared epitaxial wafer is subjected to substrate thinning and distributed Bragg reflector (DBR) coating, and then cut, wire bonded and TO packaged (the packaging material includes resin) to obtain a Micro-LED chip.

[0075] Example 2

[0076] This embodiment is basically the same as the embodiment 1, except that: based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer 9 is 25%, that is, the material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.25 Ga0.75 N. The p-type AlGaN electron blocking layer 9 is doped with Mg, and the Mg doping concentration is the same as that in Example 1. The thickness of the p-type AlGaN electron blocking layer 9 is 12 nm. The rest is the same as that in Example 1.

[0077] Example 3

[0078] This embodiment is basically the same as the embodiment 1, except that: based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer 9 is 29%, that is, the material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.29 Ga 0.71 N. The p-type AlGaN electron blocking layer 9 is doped with Mg, and the Mg doping concentration is the same as that in Example 1. The thickness of the p-type AlGaN electron blocking layer 9 is 8 nm. The rest is the same as that in Example 1.

[0079] Comparative Example 1

[0080] This comparative example is basically the same as Example 1, except that: based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer 9 is 20%, that is, the material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.2 Ga 0.8 N. The p-type AlGaN electron blocking layer 9 is doped with Mg, and the Mg doping concentration is the same as that in Example 1. The thickness of the p-type AlGaN electron blocking layer 9 is still 10 nm. The rest is the same as that in Example 1.

[0081] Comparative Example 2

[0082] This comparative example is basically the same as Example 1, except that: based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer 9 is 35%, that is, the material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.35 Ga 0.65 N. The p-type AlGaN electron blocking layer 9 is doped with Mg, and the Mg doping concentration is the same as that in Example 1. The thickness of the p-type AlGaN electron blocking layer 9 is still 10 nm. The rest is the same as that in Example 1.

[0083] Comparative Example 3

[0084] This comparative example is basically the same as Example 1, except that the thickness of the p-type AlGaN electron blocking layer 9 is 20 nm. The material of the p-type AlGaN electron blocking layer 9 includes p-Al 0.27 Ga 0.73N is the same as in Example 1. The p-type AlGaN electron blocking layer 9 is doped with Mg element, and the doping concentration of Mg is the same as in Example 1. The rest is the same as in Example 1.

[0085] Test Example 1

[0086] The LED devices (i.e., LED epitaxial wafers) of Examples 1-3 and Comparative Examples 1-3 were subjected to surface indium sphere testing under the same electrical injection conditions (10 mA). The test system employed primarily includes a manual probe station and an integrating sphere. The specific functions and parameters of each module of the test system are as follows: The manual probe station, model FormFactor EPS150TRIAX, electrically connects the epitaxial wafer sample to the digital source meter by adjusting the three-dimensional probe holder and provides support for the integrating sphere; the integrating sphere, model Instrument Systems ISP 75, receives the light emitted by the epitaxial wafer sample.

[0087] The method of surface point indium ball test is: pierce the indium ball with a metal probe and apply current (10mA) to light it up for test.

[0088] Figure 3 This is a point-to-point luminescence photograph of Example 1 ( Figure 3 The left figure in the figure) and the integrating sphere light collection spectra of Example 1 and Comparative Examples 1-3 ( Figure 3 (right image in the figure). Figure 3 It can be seen that compared to Example 1, the emission wavelengths of Comparative Examples 1 and 3 are both shorter and the spot-measured intensities are lower. Although the emission wavelength of Comparative Example 2 is similar to that of Example 1, the spot-measured intensity is significantly lower than that of Example 1 due to the excessively high Al content in the EBL. The spot-measured intensity reflects the luminescence intensity, so Example 1 has a higher luminescence intensity than Comparative Examples 1-3. Furthermore, the peak wavelength of Example 2 is 622.2 nm, while that of Example 3 is 622.7 nm. Furthermore, the spot-measured intensities of Examples 2 and 3 are close to those of Example 1.

[0089] Test Example 2

[0090] The test system used in this test case mainly includes: a high-precision fast spectroradiometer, an integrating sphere, and a digital source meter. The specific functions and parameters of each module of the test system are as follows:

[0091] (1) High-precision, fast spectroradiometer: Model: Yuanfang HAAS-2000, connected to an integrating sphere to measure the optical characteristics of Micro-LED chip samples. Key technical specifications include: spectral range 380-780nm; wavelength accuracy ±0.3nm, optical bandwidth 2.5nm; and luminous flux measurement range 0.01-2000lm.

[0092] (2) Integrating Sphere: This is a 50cm diameter integrating sphere specifically designed for YuanFang LEDs. The sample is placed inside the sphere, which receives the sample's light at a 360° angle. The integrating sphere's Shibelen R98 coating achieves 97% reflectivity in the visible range, offers high long-term stability, and is suitable for the 380-1500nm spectral range.

[0093] (3) Digital Source Meter: Model Keithley 2430, used to apply electrical signals to Micro-LED chip samples and perform electrical tests.

[0094] Figure 4 The Micro-LED chip made of the InGaN red LED device of Example 1 was tested using the above test system at different electrical injection ( Figure 4 Performance test results under the conditions indicated in the table. Figure 4 The test results of LED chips with different diameters (5μm, 10μm, 15μm, 20μm) are shown in Figure 2. Figure 4 It can be seen that the Micro-LED chip of Example 1 has both a higher peak wavelength and a higher wall-plug efficiency (WPE). Figure 5 Peak wavelength curves of the Micro-LED chip (diameter 15 μm) made of the InGaN red LED device of Example 1 and Comparative Example 1 under different electrical injections. Figure 5 It can be seen that compared with Comparative Example 1, Example 1 of the present invention increases the emission wavelength of the InGaN red light LED by controlling the Al component content and thickness in the p-type AlGaN electron blocking layer, thereby achieving long-wavelength emission in the low-In component active region.

[0095] Test Example 3

[0096] The atomic percentage of Al in the p-type AlGaN electron blocking layer 9 was adjusted to 0% (i.e., forming a GaN layer), 5%, 10%, 15%, 20% (i.e., Comparative Example 1), 23%, 25%, and 30%, respectively. The atomic percentage of Al is based on the total number of Al and Ga atoms in AlGaN being 100%. The thickness of the p-type AlGaN electron blocking layer 9 was 10 nm. The rest of the contents were the same as in Example 1, thereby obtaining different Micro-LED chips. These Micro-LED chips were simulated using SiLENSe software to obtain peak wavelength curves for different Al component contents, as shown in FIG. Figure 6 As shown. Figure 6 Combine Figure 3 It can be seen that by controlling the Al component content in the p-type AlGaN electron blocking layer 9 and the thickness of the p-type AlGaN electron blocking layer within the range of the present invention, the polarization effect can be enhanced, thereby increasing the luminous wavelength while also taking into account a higher luminous intensity. Figure 6 The comparative examples in which the atomic percentage of Al is not within the range of the present invention cannot achieve the effects of increasing the luminous wavelength and increasing the luminous intensity at the same time.

Claims

1. An InGaN red light LED device based on a variable Al composition electron blocking layer to enhance the polarization effect, which comprises, from bottom to top: A substrate, a low-temperature buffer layer grown on the substrate, a high-temperature buffer layer grown on the low-temperature buffer layer, a non-doped GaN layer grown on the high-temperature buffer layer, an n-type doped GaN layer grown on the non-doped GaN layer, a superlattice layer and / or a low-temperature GaN layer grown on the n-type doped GaN layer, a quantum well active region grown on the superlattice layer or the low-temperature GaN layer, a p-type AlGaN electron blocking layer grown on the quantum well active region, and a p-type region grown on the p-type AlGaN electron blocking layer; wherein the quantum well active region comprises a composite layer of a red light quantum well layer-a red light barrier layer; based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer is 22-30%; and the thickness of the p-type AlGaN electron blocking layer is 5-15nm.

2. The InGaN red LED device according to claim 1, wherein: The material of the low-temperature buffer layer includes GaN material, and the growth temperature is 550-600°C; the material of the high-temperature buffer layer includes GaN material, and the growth temperature is 1000-1050°C; Preferably, the low-temperature buffer layer has a thickness of 0.2-0.5 μm; and the high-temperature buffer layer has a thickness of 0.1-0.5 μm.

3. The InGaN red LED device according to claim 1, wherein: The thickness of the non-doped GaN layer is 2-4 μm.

4. The InGaN red LED device according to claim 1, wherein: The thickness of the n-type doped GaN layer is 1-3 μm; Preferably, the doping element in the n-type doped GaN layer is silicon, and the doping concentration is 1E18-5E18 cm -3 .

5. The InGaN red LED device according to claim 1, wherein: The superlattice layer includes an InGaN / GaN superlattice with a period number of 2-30 periods; Preferably, the InGaN / GaN superlattice comprises an InGaN layer with a thickness of 1-3 nm and a GaN layer with a thickness of 2-15 nm; Preferably, based on the total number of In and Ga atoms in the InGaN layer in the InGaN / GaN superlattice being 100%, the content of In in the InGaN layer is 3-8%.

6. The InGaN red LED device according to claim 5, wherein: The superlattice layer is a silicon-doped superlattice layer or a non-doped superlattice layer; Preferably, the superlattice layer is a silicon-doped superlattice layer with a doping concentration of 1E18-5E18 cm -3 .

7. The InGaN red LED device according to claim 1, wherein: The material of the low-temperature GaN layer includes non-doped GaN material, and the growth temperature is 700-850° C.; Preferably, the thickness of the low-temperature GaN layer is 5-100 nm.

8. The InGaN red LED device according to claim 1, wherein: The quantum well active region includes a composite layer of a red light quantum well layer-red light barrier layer with a period number of 1-5 periods; Preferably, the material of the red light quantum well layer comprises a non-doped InGaN material, wherein the atomic percentage of In is 25-35%, based on the total atomic number of In and Ga in the non-doped InGaN material being 100%; Preferably, the thickness of the red light quantum well layer is 2-4 nm; Preferably, the material of the red light barrier layer comprises an undoped GaN material or an undoped InGaN material, and the atomic percentage of In in the red light barrier layer is 0-10%, based on the total number of In and Ga atoms in the undoped GaN material or the undoped InGaN material being 100%. Preferably, the thickness of the red light barrier layer is 3-20 nm.

9. The InGaN red LED device according to claim 1, wherein: The quantum well active region further comprises a composite layer of a blue light quantum well layer-a blue light barrier layer having a period number of 1-5 periods, and the composite layer of a red light quantum well layer-a red light barrier layer is grown on the composite layer of a blue light quantum well layer-a blue light barrier layer; Preferably, the material of the blue light quantum well layer comprises a non-doped InGaN material, wherein the atomic percentage of In is 3-10%, based on the total atomic number of In and Ga in the non-doped InGaN material being 100%; Preferably, the thickness of the blue light quantum well layer is 2-4 nm; Preferably, the material of the blue light barrier layer comprises an undoped GaN material or an undoped InGaN material, and the atomic percentage of In in the blue light barrier layer is 0-5%, based on the total atomic number of In and Ga in the undoped GaN material or the undoped InGaN material being 100%. Preferably, the thickness of the blue light barrier layer is 3-20 nm.

10. The InGaN red LED device according to claim 1, wherein: Taking the total number of Al and Ga atoms in AlGaN as 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer is 25-29%; the thickness of the p-type AlGaN electron blocking layer is 8-12 nm; Preferably, based on the total number of Al and Ga atoms in AlGaN being 100%, the atomic percentage of Al in the p-type AlGaN electron blocking layer is 27%; the thickness of the p-type AlGaN electron blocking layer is 10 nm; Preferably, the p-type AlGaN electron blocking layer is doped with Mg element, and the doping concentration of Mg is 1E18-2E20 cm -3 .

11. The InGaN red LED device according to claim 1, wherein: The material of the p-type region includes GaN material and is doped with Mg element, and the doping concentration of Mg is 1E18-2E20 cm -3 ; Preferably, the thickness of the p-type region is 100-300 nm.

12. A method for preparing an InGaN red light LED device based on a variable Al composition electron blocking layer to enhance polarization effect as claimed in any one of claims 1 to 11, comprising the following steps: (1) epitaxially growing a low-temperature buffer layer, a high-temperature buffer layer, a non-doped GaN layer, an n-type doped GaN layer, a superlattice layer and / or a low-temperature GaN layer in sequence on a substrate; (2) epitaxially growing a quantum well active region on the superlattice layer or the low-temperature GaN layer; (3) epitaxially growing a p-type AlGaN electron blocking layer and a p-type region on the quantum well active region in sequence, thereby obtaining the InGaN red light LED device based on a variable Al composition electron blocking layer to enhance the polarization effect.

13. The preparation method according to claim 12, wherein: Step (1) comprises: epitaxially growing a low-temperature buffer layer, a high-temperature buffer layer, a non-doped GaN layer, an n-type doped GaN layer, a superlattice layer and / or a low-temperature GaN layer on a substrate in sequence by using an MOCVD epitaxial growth method, wherein the growth conditions comprise: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an In source flow rate of 20-300 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the low-temperature buffer layer of 550-600° C.; a growth temperature of the high-temperature buffer layer of 1000-1050° C.; a growth temperature of the non-doped GaN layer of 1000-1050° C.; a growth temperature of the n-type doped GaN layer of 1000-1050° C.; a growth temperature of the superlattice layer of 700-850° C.; and a growth temperature of the low-temperature GaN layer of 700-850° C.

14. The preparation method according to claim 12, wherein: Step (2) comprises: epitaxially growing a quantum well active region on the superlattice layer or the low-temperature GaN layer by using an MOCVD epitaxial growth method, wherein the region comprises a composite layer of a red light quantum well layer and a red light barrier layer, and the growth conditions comprise: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an In source flow rate of 20-500 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the red light quantum well layer of 650-730° C.; and a growth temperature of the red light barrier layer of 750-900° C.; Preferably, the quantum well active region further includes a composite layer of a blue light quantum well layer-blue light barrier layer with a period number of 1-5 periods, and the composite layer of the red light quantum well layer-red light barrier layer is grown on the composite layer of the blue light quantum well layer-blue light barrier layer; the growth conditions of the composite layer of the blue light quantum well layer-blue light barrier layer include: growth pressure of 50-1000mbar, Ga source flow rate of 10-200sccm; In source flow rate of 20-500sccm; N source flow rate of 2-10slm; carrier gas of nitrogen or hydrogen; growth temperature of the blue light quantum well layer of 720-750℃; growth temperature of the blue light barrier layer of 750-900℃.

15. The preparation method according to claim 12, wherein: Step (3) comprises: epitaxially growing a p-type AlGaN electron blocking layer and a p-type region on the quantum well active region in sequence by using an MOCVD epitaxial growth method, wherein the growth conditions comprise: a growth pressure of 50-1000 mbar, a Ga source flow rate of 10-200 sccm; an Al source flow rate of 10-400 sccm; an N source flow rate of 2-10 slm; a carrier gas of nitrogen or hydrogen; a growth temperature of the p-type AlGaN electron blocking layer of 900-1000° C.; and a growth temperature of the p-type region of 900-1000° C.

Citation Information

Patent Citations

  • Epitaxial growth method for improving GaN-based light-emitting diode (LED) quantum well structure to improve carrier recombination efficiency

    CN102881788A

  • Preparation method of InGaN / GaN multi-quantum well-based red light LED structure

    CN111916538A

  • Realize short wavelength's ultraviolet LED's epitaxial structure

    CN206742273U

  • Nonpolar ultraviolet LED

    CN208014734U

Cited By

  • AlGaInP red light Micro-LED chip with high Al component polarization induced barrier layer and preparation method of AlGaInP red light Micro-LED chip

    CN122294659A

  • Algalnp red light micro-led chip with high al component polarization induced barrier layer and preparation method

    CN122294659B